Independent and Combined Effects of All-Out Sprint and Low-Intensity Continuous Exercise on Plasma Oxidative Stress Biomarkers in Trained Judokas - El Abed, Kais; Ammar, Achraf; Boukhris, Omar; Trabelsi, Khaled; Masmoudi, Liwa; Bailey, Stephen J.; Hakim, Ahmad; Bragazzi, Nicola Luigi (Frontiers in Physiology, 2019)
The purpose of this study was to assess oxidative stress biomarkers prior to and following different forms of exercise. Ten elite male judokas (age: 18.1 ± 1.7 years, athletic experience: 6 years with a training frequency of 6 Judo-sessions/week) performed three cycle ergometry sessions comprising a 30 s Wingate test (MAX), 30 min at 60% maximal-aerobic-power-output (LOW) or these two exercise protocols combined (COMBINED) in a repeated-measures design. Venous blood-samples were collected before, and 0(P0), 5(P5), 10(P10) and 20(P20) min after each exercise protocol and assessed for malondialdehyde concentration ([MDA]), glutathione peroxidase (GPX), superoxide dismutase (SOD) and glutathione reductase (GR) content, and total-antioxidant-status (TAS). Plasma [MDA] was found to be increased above baseline at P0 and P5 in the MAX, LOW and COMBINED conditions (p < 0.05), but was greater at P10 and P20 in the LOW condition compared to MAX and COMBINED conditions (p < 0.05). Blood GPX and SOD content increased above baseline at P0 in MAX and COMBINED and at P5 in LOW (p < 0.05), with GR content being similar between groups at P0 and P5 (p > 0.05). 20 min post-exercise, GPX, SOD, GR content and TAS were lower in the MAX compared to the LOW and COMBINED conditions (p < 0.05). In conclusion, the findings from this study reveal that redox-related biomarkers exhibited divergent response dynamics following different forms of exercise, which might have implications for understanding the mechanisms of exercise-induced skeletal muscle fatigue and adaptive remodeling.